THE COMMUNICATIVE METHOD IN TEACHING SPEAKING IN ENGLISH - Sadikova Suriya Saidovna; Mahammadiyeva Guldasta; Boʻltakova Ozoda Husniddin qizi (Journal of new century innovations, 2023)
Abstract This article describes the applicability of the communicative method to teaching speaking in English as a foreign language. In addition to describing the principles of the communicative method in teaching a foreign language, the conditions necessary for the implementation of foreign language speaking are also presented, the most important of which is the presence of a speech situation serving as a potential stimulus for speaking. The communicative method implies that the process of teaching foreign language speaking is built as a model of the process of communication, which requires modeling the situation as a unit of communication and as a form of its functioning. The article also describes the functions of speech situations and their classification.